(untitled) (Journal of Rangpur Medical College, 2026)
Background: Pediatric pleural effusions arise from diverse etiologies, with tuberculous pleural effusion (TPE) and non-tuberculous causes being the most common. Early differentiation is essential for timely management. Objective: This study aimed to evaluate the diagnostic significance of pleural fluid ADA and hematological parameters in distinguishing pediatric tubercular versus non-tubercular pleural effusions. Methods: A cross-sectional study was conducted at Bangladesh Shishu Hospital and Institute from July 2019 to January 2022, including 47 children aged 1-18 years with pleural effusion. The diagnostic performance of pleural fluid ADA and key hematological parameters was analyzed using SPSS 26. Results: Pleural ADA was markedly higher in TPE than in non-TPE cases (90.6±52.0 vs. 36.0±11.5 U/L). TPE patients showed significantly lower total WBC counts and polymorph percentages, but higher lymphocyte percentages and ESR (P<0.05). Hemoglobin, platelet count, and CRP showed no significant group differences. Conclusion: Pleural fluid ADA, combined with selected haematological parameters, provides meaningful discrimination between tubercular and non-tubercular pediatric pleural effusions and supports clinical decision-making. J Rang Med Col.2026 Mar;11(1):172-176